Study and optimization of perovskite-based solar cells - Abdelkader, HIMA (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2020)
Abstract Renewable energy technologies are in plain evolution due to the international de- mand of electric power and the pollutant fossil energy depletion. Since a while, Researches in the field of solar energies are in exponential evolution, and the use of new generation photovoltaics is attracting researchers attention. One of the most new generation solar cell promising technologies is the introduction of perovskite materials. These latter have some important characteristics suit- able for solar energy harvesting namely adapted band gap to solar radiation absorption, abundant materials in the nature, low cost processing and excel- lent absorption factor. In this thesis, solar cells based on perovskite materials have been proposed and investigated in order to enhance the power conversion efficiency of the devices. These materials include methyl ammonium lead tri- iodide (MAPbI3), methyl ammonium tin tri-iodide (MASnI3) and methyl ammo- nium germanium tri-iodide (MAGeI3). Different structures of solar cells based on MAPbI3 and MASnI3 are numerically modeled using the ATLAS-Silvaco and SCAPS softwares to improve their performances. Therefore, an optimization pro- cess is applied to these structures to find the better power conversion efficiency of solar cells. In addition, Ge-perovskite solar cell designs are studied and in- vestigated to improve the performance of these devices. Moreover, diverse kinds of electron transporting layers (ETLs) and hole transporting layers (HTLs) are inserting in Ge-perovskite solar cell in order to enhance the power conversion efficiency of perovskite devices. Found results shows that the n-i-p structure of TiO2 \ MASnI3 \ spiro-OMeTAD with layer thickness of 100 nm, 500 nm, and 200 nm respectively gives a Power conversion efficiency of 9.56%. It is to under- line the new proposed and optimized structure based on non-toxic p-i-n structure CuSBS2 \ CH3NH3GeI3 \ C60 with layer thickness of 50 nm, 950 nm, and 50 nm respectively gives a high power conversion efficiency of 23.58%. Thus, the ob- tained results potentialy provide a guidance for design and fabrication of future Ge-perovskite solar cells for enhanced power conversion efficiency.
Thèses de Doctorat of Science in Electronics in scientifique technologie
Keywords: Perovskite, Photovoltaic solar cell, Silvaco Atlas, SCAPS, I-V char- acteristics, power conversion efficiency.; ا"رو% ت، ا21 ا #روو! ، $% و أطس، ا1* V-I، ردود ا &ول اط وي .